Pengaruh Pengalaman Magang, Kompetensi Kerja, dan Adaptabilitas Karier terhadap Kesiapan Kerja Mahasiswa Manajemen Universitas Maritim Raja Ali Haji (International Forum of Researchers and Lecturers, 2026)
This study aims to examine the influence of internship experience, work competencies, and career flexibility on the employability readiness of students from the Management Study Program at Universitas Maritim Raja Ali Haji in entering the workforce. A survey method with a quantitative approach was applied to 114 respondents selected randomly. Data was collected through questionnaires and analyzed using multiple linear regression with SPSS version 22. The results show that internship experience does not significantly affect students' readiness to enter the workforce. However, work skills and career flexibility variables have a positive and significant impact on employability readiness. Overall, these three factors contribute positively and significantly to students' readiness to enter the workforce. The findings highlight the importance of integrated development within the higher education curriculum, including improving work skills and career adaptation to better prepare students for professional challenges. Therefore, higher education institutions need to consider these factors when designing more relevant and adequate educational programs for students.